2021
DOI: 10.32890/ijbf2021.16.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Financial Distress in Malaysia and Its Effect on Stock Returns

Abstract: Unstable economic conditions have an adverse impact on the financial performance of firms, leading to financial distress, which is an unfavourable situation for investors as it may affect their investment returns. Thus, this study attempted to predict financial distress and to examine the effect of financial distress on stock returns by using firms listed on Bursa Malaysia from 1990 to 2020. This study used the logit model to find the probability of bankruptcy and also as a proxy for financial distress risk in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…Conversely, a study by Muzharoatiningsih & Hartono (2022) indicated that company growth doesn't significantly affect financial distress, a conclusion mirroring the findings of Saputra & Salim (2020). When evaluating the impact of the interest coverage ratio on financial distress, Meryana & Setiany (2021) contend that the ratio significantly influences financial distress, a sentiment echoed by Hanafi et al (2021), Shetty & Vincent (2021), and Abu Bakar & Yahya (2021).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Conversely, a study by Muzharoatiningsih & Hartono (2022) indicated that company growth doesn't significantly affect financial distress, a conclusion mirroring the findings of Saputra & Salim (2020). When evaluating the impact of the interest coverage ratio on financial distress, Meryana & Setiany (2021) contend that the ratio significantly influences financial distress, a sentiment echoed by Hanafi et al (2021), Shetty & Vincent (2021), and Abu Bakar & Yahya (2021).…”
Section: Introductionmentioning
confidence: 93%
“…High sales growth values indicate a company's adeptness in executing product sales and marketing strategies, offering signals to financial statement users (Prasetya & Oktavianna, 2021). Hanafi et al (2021) point out that increasing corporate debt can erode profits, leading to financial distress. Conversely, companies with significant fixed assets are perceived to be more secure due to their potential use as collateral, thereby diminishing financial distress risks (Akmalia, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The study measured the performance of the two models using rate, type I error, and type II error and concluded that the logit model performed better with a higher accuracy rate and lower type I and type II error values. The study by Hanafi et al (2021), which examined the effect of financial distress on stock returns using firms listed on Bursa Malaysia and a logit model, found that the risk of financial distress had no significant impact on pricing stock returns across all tested models. Horváthová and Mokrišová (2020) used the data envelopment analysis (DEA) model and verified the estimation accuracy of this model in comparison with the logit model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For large companies, financial distress significantly results in significant losses for investors, creditors, and stakeholders, impacting firm value (Arora & Saurabh, 2022). Hanafi et al (2021) state that management must apply the precautionary principle in managing finances because it will impact the risk of financial distress. Creditors and investors must make forecasts to measure the level of risk of financial distress.…”
Section: Firm Size and Firm Valuementioning
confidence: 99%